Upaya dalam Menangani Problem Etika dalam Fisafat Ilmu - Mardinal Tarigan; Sania Oktavia Nasution; Siti Sholikhah; Najwa Al Zuhda Sitorus; Dwi Fathimah (Universitas Muhammadiyah Enrekang, 2022)
Philosophy of science is a true knowledge that occurs in a judicial manner regarding an object of knowledge obtained from a point of view or method used. According to one expert says that